REPRESENTASI KONSEP DIRI DALAM FILM "MAU JADI APA?" (ANALISIS SEMIOTIKA JOHN FISKE) - Arinta Putri Anggraini, (2022)
Mau Jadi Apa is a student comedy drama film directed by Monty Tiwa and Soleh Solihun and produced by Starvision Plus in 2017. This film tells about the students of Fikom Unpad and the self-concept they build through various influencing factors around them. This study aims to determine the representation of self-concept in the film Mau Jadi Apa by using John Fiske's semiotic analysis which analyzes three levels, namely the level of reality, representation, and ideology. The analysis is done by grouping the scenes in the film according to the theme of self-concept. In this study, the researcher used a descriptive qualitative approach and John Fiske's semiotic analysis method consisting of television codes, to find out the scenes that contained the meaning of self-concept and were also reinforced by the journals and articles that the researchers studied. The results of this study have a meaning, namely the form of representation of positive and negative self-concepts in college life is reflected in various aspects ranging from family relationship patterns to age maturity and mindset. This is still relevant today because each individual continues to develop over time, this is illustrated through John Fiske's level of semiotic analysis, namely reality, representation, and ideology.